2019
DOI: 10.1002/cam4.2074
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic expression of human airway trypsin‐like protease 4 in acute myeloid leukemia promotes cancer cell invasion and tumor growth

Abstract: Transmembrane serine proteases have been implicated in the development and progression of solid and hematological cancers. Human airway trypsin‐like protease 4 (HAT‐L4) is a transmembrane serine protease expressed in epithelial cells and exocrine glands. In the skin, HAT‐L4 is important for normal epidermal barrier function. Here, we report an unexpected finding of ectopic HAT‐L4 expression in neutrophils and monocytes from acute myeloid leukemia (AML) patients. Such expression was not detected in bone marrow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…As MC concentration increased, the position of the highest absorption peak of TRP had a red shift from 280 nm to 285 nm. The results showed that the binding of MC to the base pair of TRP resulted in a π-π * transition of amino acid residues in TRP, which reduced the energy and changed the conformation of the protein [ 27 ]. The absorbance of the maximum absorption peak of TRP increased noticeably, and only a static quenching absorption spectrum changes with a change of ground state molecule.…”
Section: Resultsmentioning
confidence: 99%
“…As MC concentration increased, the position of the highest absorption peak of TRP had a red shift from 280 nm to 285 nm. The results showed that the binding of MC to the base pair of TRP resulted in a π-π * transition of amino acid residues in TRP, which reduced the energy and changed the conformation of the protein [ 27 ]. The absorbance of the maximum absorption peak of TRP increased noticeably, and only a static quenching absorption spectrum changes with a change of ground state molecule.…”
Section: Resultsmentioning
confidence: 99%
“…Also TMPRSS11F was identified to gain AR-association in VCaP-CT cells. This particular member of the gene family has not been widely studied but it has been reported to contribute to tumor growth and poor outcome in acute myeloid leukemia patients [ 93 ]. Nevertheless, our results suggest different role for TMPRSS11F in prostate cancer as its low expression was associated with poor progression-free survival and high Gleason score and T-stage.…”
Section: Discussionmentioning
confidence: 99%
“…She is involved in processes of proliferation, invasion and metastasis in colorectal cancer. 15,16 Digestion of type II collagen by trypsin promotes invasion of the basement membrane. In addition, the activation of trypsin in tumor cells and the co-expression of MMPs facilitate invasion and metastasis.…”
Section: Tumoral Proteasesmentioning
confidence: 99%